Short-term outcomes from drug-coated balloon for coronary de novo lesions in large vessels. Issue 2 (February 2019) - Lu, Wenjie; Zhu, Yongjian; Han, Zhanying; Sun, Guoju; Qin, Xiaofei; Wang, Zhengbin; Liu, Guanghui; Xi, Wang; Wang, Xule; Pan, Liang; Qiu, Chunguang
Highlights: The drug-coated balloon (DCB) only strategy is safe and efficient in large coronary artery lesions. Some dissections after DCB treatment could spontaneously heal. "Late lumen enlargement" after DCB dilatation may also occur in large vessels. Abstract: Background: A drug-coated balloon (DCB) has been designed as a new device for the treatment of coronary artery disease. The data regarding DCB-treated lesions in large coronary artery are limited. The purpose of our study was to explore the effectiveness and safety of DCB in large coronary artery. Methods: We prospectively analyzed all patients treated with DCB in de novo lesions consistent with inclusion criteria between May 2015 and April 2017. The observed outcomes included target lesion revascularization (TLR), myocardial infarction, cardiac death and non-cardiac death, and major adverse cardiac events (MACE). Results: There were 92 patients including 94 coronary de novo lesions treated in all. The most often utilized DCB diameters were 3.0 mm (41.5%) and 3.5 mm (39.4%). Two acute closures occurred in hospital. Six bailout drug-eluting stents were used in the percutaneous coronary interventions (6.4%). Quantitative coronary angiography measurement at follow-up showed late lumen loss was -0.02 ± 0.49 mm. The TLR rate and overall MACE rates were 4.3% and 4.3% during the follow-up period in the whole patient population, respectively. Conclusions: Our study showed that the "DCB only" strategy is safe and efficient in large vessel lesions of patients whose predilation achieved an acceptable result.